SEXUALITY AND SEXUAL POLITICS IN CONTEMPORARY INDONESIA - Arivia, Gadis (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
The post-Suharto period was expected to establish Indonesiaas a democracy, committed to equality between citizens andhuman rights, but respect for women's equal rights, for examplethe freedom to terminate a pregnancy, freedom of expression,freedom from polygamy, has not occurred. Indonesia hasenjoyed some expanded political liberties, but the civil libertiesof the Indonesian people are not protected. Why hasdemocracy failed to deliver civil liberties in Indonesia despite itssuccess in opening up political liberties? Why has democracystrengthened the ties between the government and dominantreligious institutions? These are the questions I address. In thecase of Indonesia, the transition to democracy has notnecessarily led to the liberalization concerning laws on genderand freedom of the individual. In fact it has led to the opposite.This is true in the case of women's sexual liberation, which iscondemned and restricted both by the democratic electedgovernment and the dominant religious institutions.